A case of penile strangulation after placement of metallic rings - Iraklis C Mitsogiannis; Nikolaos Kostakopoulos; Lazaros Lazarou; Evangelos Karagiotis (Urology Annals, 2018)
Penile strangulation following placement of metallic rings is a rare clinical entity that needs urgent attention to avoid potentially severe clinical consequences. Careful handling and occasionally a multidisciplinary approach are the keys to a successful outcome.